The prologue of Euripides' Oedipus - Prodi, E (Svenska Klassikerförbundet, 2017)
The article reexamines the evidence for the prologue of Euripides’ lost Oedipus (fr. 539a Kannicht) and makes some suggestions concerning the identity of the speaker and the train of thought of the prologue.